KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA KE FILM BULAN TERBELAH DI LANGIT AMERIKA KARYA SUTRADARA RIZAL MANTOVANI - Wahyuni, Fuji; Hayati, Yenni; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2017)
The purpose of this article (a) to describe story of episode novel Bulan Terbelah di Langit Amerika created by Hanum Salsabiela Rais and Rangga Almahendra, (b) to describe story of episode film Bulan Terbelah di Langit Amerika director by Rizal Mantovani, (c) to describe similiar and different story of episode novel with film Bulan Terbelah di Langit Amerika. The data of this study were story of episode novel Bulan Terbelah di Langit Amerika created by Hanum Salsabiela Rais and Rangga Almahendra and film Bulan Terbelah di Langit Amerika director by Rizal Mantovani. Analyzed technique do with ekranisasi theory. The findings of the study showed that the decrease story of episode and sub episode novel Bulan Terbelah di Langit Amerika created by Hanum Salsabiela Rais and Rangga Almahendra in film Bulan Terbelah di Langit Amerika director by Rizal Mantovani become to story of episode to 87 story of episode. Increase story of episode in film Bulan Terbelah di Langit Amerika director by Rizal Mantovani become to 32 story of episode. The same variation changes event, figure and background story ofepisode in novel Bulan Terbelah di Langit Amerika created by Hanum Salsabiela Rais and Rangga Almahendra and film Bulan Terbelah di Langit Amerika director by Rizal Mantovani become to 25 story of episode.Keywords: novel, film, ecranization, story of episode